Dynamics of Photoinduced Charge Carrier and Photothermal Effect in Pulse-Illuminated Narrow Gap and Moderate Doped Semiconductors - Slobodanka Galovic; Katarina Djordjevic; Milica Dragas; Dejan Milicevic; Edin Suljovrujic (Mathematics)
When a sample of semiconducting material is illuminated by monochromatic light, in which the photon energy is higher than the energy gap of the semiconductor, part of the absorbed electromagnetic energy is spent on the generation of pairs of quasi-free charge carriers that are bound by Coulomb attraction. Photo-generated pairs diffuse through the material as a whole according to the density gradients established, carrying part of the excitation energy and charge through the semiconducting sample. This energy is indirectly transformed into heat, where the excess negatively charged electron recombines with a positively charged hole and causes additional local heating of the lattice. The dynamic of the photoexcited charge carrier is described by a non-linear partial differential equation of ambipolar diffusion. In moderate doped semiconductors with a low-level injection of charge carriers, ambipolar transport can be reduced to the linear parabolic partial differential equation for the transport of minority carriers. In this paper, we calculated the spectral function of the photoinduced charge carrier distribution based on an approximation of low-level injection. Using the calculated distribution and inverse Laplace transform, the dynamics of recombination photoinduced heat sources at the surfaces of semiconducting samples were studied for pulse optical excitations of very short and very long durations. It was shown that the photoexcited charge carriers affect semiconductor heating depending on the pulse duration, velocity of surface recombination, lifetime of charge carriers, and their diffusion coefficient.